Relativistic effects on the nuclear magnetic shielding tensor - Melo, J.I. (2003)
A two-component theory for shielding calculations starting from a four-component Rayleigh-Schrodinger perturbation theory (RSPT) formalism is presented. Thus, a set of operators entering the RSPT expressions in terms of the Schrodinger molecular spectrum are derived by expanding such four-component expression as a power series in c-1. All formal expressions are retained, without neglecting any terms in the intermediate steps of the derivation.